2016
DOI: 10.1074/jbc.m115.683912
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput Functional Genomics Identifies Regulators of Primary Human Beta Cell Proliferation

Abstract: The expansion of cells for regenerative therapy will require the genetic dissection of complex regulatory mechanisms governing the proliferation of non-transformed human cells. Here, we report the development of a high-throughput RNAi screening strategy specifically for use in primary cells and demonstrate that silencing the cell cycle-dependent kinase inhibitors CDKN2C/p18 or CDKN1A/p21 facilitates cell cycle entry of quiescent adult human pancreatic beta cells. This work identifies p18 and p21 as novel targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 49 publications
3
48
0
Order By: Relevance
“…156,157 Phosphatase and tensin homolog (PTEN) activation, which contributes to β-cell failure in mouse models of type 2 diabetes, 158 was increased in Mir155 -/-Ldlr -/-mice (Figure 36). Moreover, glucose transporter (Glut)2-dependent pathways and pathways related to cyclic adenosine monophosphate (AMP), GLP-1, and glucose-dependent insulinotropic polypeptide (GIP) signaling were inhibited, suggesting impaired glucose uptake and insulin secretion (Figure 36).…”
Section: Effect Of Mir-155 On Global Gene Expression In Pancreatic Ismentioning
confidence: 99%
“…156,157 Phosphatase and tensin homolog (PTEN) activation, which contributes to β-cell failure in mouse models of type 2 diabetes, 158 was increased in Mir155 -/-Ldlr -/-mice (Figure 36). Moreover, glucose transporter (Glut)2-dependent pathways and pathways related to cyclic adenosine monophosphate (AMP), GLP-1, and glucose-dependent insulinotropic polypeptide (GIP) signaling were inhibited, suggesting impaired glucose uptake and insulin secretion (Figure 36).…”
Section: Effect Of Mir-155 On Global Gene Expression In Pancreatic Ismentioning
confidence: 99%
“…While several of these have clear activity in rodent islets, none have proven useful in stimulating human β-cell proliferation. This inability to stimulate human β-cell proliferation has led to intense efforts by several groups to use high-throughput small-molecule screening approaches to identify compounds or small molecules that stimulate β-cell proliferation [811]. Interestingly, recent, independent discoveries have identified the dual-specificity tyrosine-regulated kinase-1a (DYRK1A) as the likely target of compounds such as harmine and 5-iodotubercidin, both of which stimulate adult human β-cell proliferation [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, recent, independent discoveries have identified the dual-specificity tyrosine-regulated kinase-1a (DYRK1A) as the likely target of compounds such as harmine and 5-iodotubercidin, both of which stimulate adult human β-cell proliferation [9,10]. Another group was able to stimulate adult human β-cell proliferation using a RNA interference strategy to silence cell cycle-dependent kinase inhibitors CDKN2C/p18 or CDKN1A/p21 and suggested that p18 and p21 may be attractive targets to promote β-cell proliferation [8]. Efforts to identify additional compounds and to optimize identified compounds are underway.…”
Section: Introductionmentioning
confidence: 99%
“…They also suggest that human β cells are more resistant to proliferation than the β cells of Rats. Recently, High-Throughput Screening methods (HTS) suggested p18 and p21 to be the prime candidates for the proliferation of beta cells [162]. …”
Section: Control Of Cell Cycle Molecules Upon β Cell Proliferationmentioning
confidence: 99%